2016
DOI: 10.1007/s40617-016-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy for Individuals with Disabilities: A Behavior Analytic Strategy for Addressing Private Events in Challenging Behavior

Abstract: Applied behavior analysts work with many populations including individuals with developmental and intellectual disabilities. Although behavior analysts have a variety of empirically supported treatments to implement when working with individuals with disabilities, sometimes, other variables may adversely impact treatment effectiveness. The degree to which problematic thoughts and feelings (private events) influence behavior may be a variable that contributes to treatment efficacy. Traditional behavior analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Few studies have assessed interventions to reduce bias or to attenuate the effects of racial bias on individuals. Most of those published focus on interventions with ACTr, which includes procedures and interventions that deal with private behaviors (Hoffmann, Contreras, Clay, & Twohig, 2016). The overall approach teaches people mindfulness, acceptance, and defusion strategies in the service of observable behaviors that align with their values, as well as skills for goal achievement.…”
Section: What Is Actr?mentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies have assessed interventions to reduce bias or to attenuate the effects of racial bias on individuals. Most of those published focus on interventions with ACTr, which includes procedures and interventions that deal with private behaviors (Hoffmann, Contreras, Clay, & Twohig, 2016). The overall approach teaches people mindfulness, acceptance, and defusion strategies in the service of observable behaviors that align with their values, as well as skills for goal achievement.…”
Section: What Is Actr?mentioning
confidence: 99%
“…Contacting the present moment is fully focusing attention on our current experiences right now, rather than in the future or the past (Hoffmann et al, 2016). Research has shown that being present in the moment can decrease stress levels for caregivers of individuals with autism (Donnchadha, 2018), increase sustained attention for children (Enoch & Dixon, 2017), and reduce implicit racial bias (Lueke & Gibson, 2015).…”
Section: What Is Actr?mentioning
confidence: 99%
See 3 more Smart Citations